2012
DOI: 10.1177/1523422312446146
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Use of Human Resource Development for Societal Development

Abstract: Author Note: This article was subjected to a two-tier, blind review process that did not involve any of the contributing authors who are currently members of the editorial board.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…One of the more exciting areas of HRD is the expanding mission of the field itself (McLean & McLean, 2001). As the mission of HRD expands into frameworks inclusive of community, national, and societal development around diverse issues of humanity and well-being (see Kim, 2012 and Kuchinke, 2010), the opportunity for HRD to impact significant research and practice is mounting. As we understand it, the evolving mission of HRD is to focus not only on outcomes, but also equally on the ways in which employees experience their environment and their work (Shuck, 2011; Wollard & Shuck, 2011).…”
Section: Emerging Implications For Hrd Practicementioning
confidence: 99%
See 1 more Smart Citation
“…One of the more exciting areas of HRD is the expanding mission of the field itself (McLean & McLean, 2001). As the mission of HRD expands into frameworks inclusive of community, national, and societal development around diverse issues of humanity and well-being (see Kim, 2012 and Kuchinke, 2010), the opportunity for HRD to impact significant research and practice is mounting. As we understand it, the evolving mission of HRD is to focus not only on outcomes, but also equally on the ways in which employees experience their environment and their work (Shuck, 2011; Wollard & Shuck, 2011).…”
Section: Emerging Implications For Hrd Practicementioning
confidence: 99%
“…Curiosity, discussion, and scholarship around the employee engagement construct in the human resource development (HRD) field have all developed robustly over the past decade. This interest has maintained course, and even stoked embers of debate long burning, as the field itself navigates evolutions of emerging missions, purposes, and boundaries (Kim, 2012; Lee, 2001; Roth, 2004). At the same time, recent study in HRD has turned attention toward understanding the connections between work, the individual experiences of work, and the unique performance connections associated with an employee’s level of engagement within his or her work (Shuck & Rocco, in press).…”
mentioning
confidence: 99%
“…In a more recent study, Blakeley and Higgs (2014) empirically showed that leaders’ abilities to understand the role of language, power, and symbolic capital were critical in developing responsible leaders. Others argued for HRD’s role in contributing to the community and broader stakeholders (Baek & Kim, 2014; Kim, 2012; Yamnill & McLean, 2013), and called for the need to utilize HRD and OD expertise to increase organizations’ responsiveness to societal and global demands (Becker et al, 2010; Stolz, 2014).…”
Section: The Csr-hr Linkmentioning
confidence: 99%
“…İnsan kaynaklarının yönetilmesi ve geliştirilmesine yönelik perspektifin çeşitli toplulukların sosyal gelişmelerinin sağlanması için uyarlanması da (Kim, 2012), örgüt ve endüstri psikolojisinin çalışma alanlarından birisini oluşturmalıdır. Ayrıca, sivil toplum kurumlarını gelecekte bekleyen sektörel gelişmeler ya da kısıtlar, bu alanda çalışan kurumların kendi ekosistemleri içinde işbirlikleri geliştirmelerini, sosyal problemlere çok paydaşlı ve bütünleştirici şekilde yaklaşmalarını da gerekli kılabilir; bu yeni koşullara sivil toplum örgütlerinin ve sivil alan çalışanlarının hazırlıklı hale getirilmesi, üstlendikleri projeleri daha etkin ve verimli şekilde gerçekleştirmeleri ve kalıcı etki yaratacak çözümlerin peşine düşmeleri gerekmektedir.…”
Section: 4unclassified